2022
DOI: 10.4103/ijcm.ijcm_825_21
|View full text |Cite
|
Sign up to set email alerts
|

“Healthy Heart, Healthy You”

Abstract: Background: Cardiovascular Disease (CVD) is the leading cause of mortality globally. Over 75% of CVD deaths occur in low- and middle-income countries. Objectives: To assess the 10-year CVD risk among adults aged 30 years and above attending the outpatient department at a Taluk Hospital, Bangalore Urban District, Karnataka. Methods: A cross-sectional study was conducted among 217 subjects above 30 years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…[ 6 ] Total number of people with CVD nearly doubled from 271 million in 1990 to 523 million in 2019, and deaths due to CVD climbed significantly from 12.1 million in 1990 to 18.6 million in 2019. [ 7 ] 32% of all fatalities worldwide in 2019 were predicted to have been caused by CVDs, causing death of 17.9 million individuals. [ 1 ] The likelihood of developing hypertension and other cardiovascular disorders increases with a higher body mass index (BMI) and weight gain in childhood, which are typically connected to a poor diet.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Total number of people with CVD nearly doubled from 271 million in 1990 to 523 million in 2019, and deaths due to CVD climbed significantly from 12.1 million in 1990 to 18.6 million in 2019. [ 7 ] 32% of all fatalities worldwide in 2019 were predicted to have been caused by CVDs, causing death of 17.9 million individuals. [ 1 ] The likelihood of developing hypertension and other cardiovascular disorders increases with a higher body mass index (BMI) and weight gain in childhood, which are typically connected to a poor diet.…”
Section: Introductionmentioning
confidence: 99%
“…While the condition surfaces during adulthood, the foundation often lies in early life choices and habits. The World Health Organization has reported that non-communicable diseases (NCDs) account for about 31% of all global deaths, with a concerning 75% of deaths occurring in low- and middle-income countries, with diabetes being the major cause next to cardiovascular diseases [ 1 ]. A majority of these deaths can be prevented as they are primarily linked to modifiable risk factors such as tobacco use, an unhealthy diet, lack of physical activity, and excessive alcohol consumption [ 2 ].…”
Section: Introductionmentioning
confidence: 99%